Azopolymers with imide structures as light-switchable membranes in controlled gas separation. (September 2019) - Bujak, Karolina; Nocoń, Klaudia; Jankowski, Andrzej; Wolińska-Grabczyk, Aleksandra; Schab-Balcerzak, Ewa; Janeczek, Henryk; Konieczkowska, Jolanta
Graphical abstract: Highlights: The main-chain azopolyimides were synthesized. The large and stable cis - trans isomerization was observed. Impact of fragility parameter on cis - trans isomerization was discussed. Azopolyimide was applied as a membrane for gas separation. Abstract: In the paper, we demonstrate a series of azobenzene polyimides with azomoieties located in the main chain for potential applications as membranes for controlled gas separation. Since azobenzene derivatives can exist in two forms, that is, thermodynamically stable trans and photoinduced cis, both isomers can be utilized for membrane preparation. The long term stability of the cis form is a precondition for such an application. Thus, the effect of polymer structure on the stability of cis - trans isomerization process in polymer films was investigated. The prepared azopolymers exhibited high stability of cis isomers and the return cis - trans reaction was not completed during 7 days after switching off the excitation light (405 nm). The stability of the cis - trans isomerization was discussed in the context of the fragility parameter. To the best of our knowledge, it is the first time when the main chain azopolymer was tested as a membrane for the gas separation. Two types of azomembranes, that is, bearing azobenzene derivatives as trans, and cis isomers and a reference membrane without azochromophore were prepared. Our investigations showed that the presence of trans -azomoieties increases the permeability of the gases (N2, O2, He and CO2 ) in comparison to the reference polyimide and that the permeability increase is not accompanied by any losses of the selectivity.